REDUCING SOCIAL EXCLUSION IN EDUCATION: A CONCEPTION OF ALL DAY SCHOOLING - Merfeldaite, Odeta; Penkauskiene, Daiva; Pivorienė, Jolanta; Railiene, Asta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Growing disproportion between different social groups, migration, unemployment, busyness of parents, not safe outside environment – there are just few general aspects of social life that influence concept and organization of all day schools. The purpose of the article is to analyse the possibilities of decreasing social exclusion in education by implementing all day school conception. In order to achieve research goal, secondary data analysis was done by applying multi stage sample. Research data shows that all day school phenomenon is not new in European education. States have to deal with inequalities in social life and education – to minimize learning results gaps, to compensate shortage of social skills, to prevent risky behaviour, to ensure safe environment and care at school and use all day school model as the mean to face these challenges. All day schools have purpose to serve as best as possible to students and their families by providing individual help, using benefits of longer time at school, specialists supervisions, community support. Social life realities and unique contexts form not unified models of all day school.